2018
DOI: 10.1016/j.cej.2018.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Continuous reactive coupling of glycerol and acetone – A strategy for triglyceride transesterification and in-situ valorisation of glycerol by-product

Abstract: Methyl esters of fatty acids are widely used as biodiesel, a sustainable replacement for petro-diesel.The conventional biodiesel process produces crude glycerol, which constitutes about 10wt% of the total products. This has led to a surplus of crude glycerol due to global increase in biodiesel use, necessitating increased research into sustainable processes that could convert the crude glycerol into higher value-added products. This study investigates biodiesel processes for continuous transesterification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 52 publications
(74 reference statements)
2
12
0
Order By: Relevance
“…Elemental analysis of the ST-DVB-SO 3 H copolymer beads showed that it contained 8.63 wt.% of sulfur, corresponding to 2.64 mmol -SO 3 H per gram of copolymer beads. The active site density of the synthesized ST-DVB-SO 3 H copolymer catalyst beads was similar to that measured for the Amberlyst TM 70, which has an acidic capacity of 2.59 mmol H + /g as measured by sulfur content elemental analysis (Eze and Harvey, 2018). It was also observed that the ST-DVB-SO 3 H had similar catalytic activity as the Amberlyst TM 70 (as shown in Figure 8).…”
Section: Catalytic Activity and Solketal Productions Using The St-dvbsupporting
confidence: 75%
“…Elemental analysis of the ST-DVB-SO 3 H copolymer beads showed that it contained 8.63 wt.% of sulfur, corresponding to 2.64 mmol -SO 3 H per gram of copolymer beads. The active site density of the synthesized ST-DVB-SO 3 H copolymer catalyst beads was similar to that measured for the Amberlyst TM 70, which has an acidic capacity of 2.59 mmol H + /g as measured by sulfur content elemental analysis (Eze and Harvey, 2018). It was also observed that the ST-DVB-SO 3 H had similar catalytic activity as the Amberlyst TM 70 (as shown in Figure 8).…”
Section: Catalytic Activity and Solketal Productions Using The St-dvbsupporting
confidence: 75%
“…Even though the reaction temperature was considered as mild, the stability of most of the solid catalysts decayed in the presence of water as a byproduct and other impurities (NaCl, methanol) from the glycerol source. The deactivation rate is even higher when the raw glycerol (contaminated with water) was fed to the reactor [106][107][108][109]. Therefore, the viability of the commercial plant depends on (i) the source of feeds [110], (ii) availability of glycerol and other feeds, and (iii) cost of glycerol as the feed.…”
Section: Perspective and Conclusionmentioning
confidence: 99%
“…In summary, although there have been previous studies on the transesterification process using ion exchange resins as a heterogeneous catalyst, some of them with very promising results, 11,[16][17][18][19][20][21][22][23] these studies have not reported the optimal parameters for the ethanolysis reaction or took into account the influence of the resin pretreatment on the conversion results. The main contribution of the present work is the optimization of operational parameters, such as temperature, catalyst amount and molar ratio, in the ethanolysis of vegetable oils using a strong anion exchange resin (Amberlyst A26OH).…”
Section: Introductionmentioning
confidence: 99%